PERKEMBANGAN LUAS LINGKUNGAN PENGENDAPAN SEDIMEN PLISTOSEN AKHIR HINGGA HOLOSEN DI DATARAN ALUVIAL RENGASDENGKLOK DAN SEKITARNYA, KAB. KARAWANG (JAWA BARAT) - Moechtar, H.; Subiyanto, Subiyanto; Samodra, H. (Pusat Survei Geologi, 2011)
Study of area development on depositional environments during the Late Pleistocene to Holocene in the alluvial plain of Rengasdengklok surroundings, Karawang Regency (West Java) based on sedimentology and stratigraphy aspects. The study was based on analyses of nine borehole informations obtained along the West to East with the thickness of sediments varied from 6.75 to 10.20 m.Study on Quaternary deposits from boreholes , revealed four depositional environments. These are swamp, floodbasin, floodplain, and river channel environments. Based on correlation of the lateral and vertical variation of the sediment bodies, three Interval of Deposition Periods were recognised. Each of the interval is characterized by increasingly and decreasingly of environments which was controlled by climatic changes and tectonic. The climatic changes were recorded as (1)minimum climate into climatic optimum under warming conditions during deposition of Interval of Deposition Period A into the middle of Interval of Deposition Period B, and (2)optimum climate into climatic minimum under cooling conditions during deposition the middle of Intreval of Deposition Period B into Interval of Deposition Period C. The tectonic activities which controlled the deposition processes were recorded as two stages. These were the change posisiton of river channel deposits 1 to river channel deposits 2 and shifting of river channel deposits 2 into Recent Citarum river (river channel deposits 3).Key words: Sediment, depositional environemnt, climate, tectonic, Rengasdengklok